2017
DOI: 10.1021/jacs.6b10608
|View full text |Cite
|
Sign up to set email alerts
|

Graded Structural Polymorphism in a Bacterial Thermosensor Protein

Abstract: Thermosensing is critical for the expression of virulence genes in pathogenic bacteria that infect warm-blooded hosts. Proteins of the Hha-family, conserved among enterobacteriaceae, have been implicated in dynamically regulating the expression of a large number of genes upon temperature shifts. However, there is little mechanistic evidence at the molecular level as to how changes in temperature are transduced into structural changes and hence the functional outcome. In this study, we delineate the conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 85 publications
6
41
0
Order By: Relevance
“…The protocols for protein purification and the majority of the spectroscopic experiments can be found in references 18 and 19. The buffers used in the pH-dependent study were glycine-HCl (pH 2–3), sodium acetate (pH 3.5–5.5), and sodium phosphate (pH 6–8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols for protein purification and the majority of the spectroscopic experiments can be found in references 18 and 19. The buffers used in the pH-dependent study were glycine-HCl (pH 2–3), sodium acetate (pH 3.5–5.5), and sodium phosphate (pH 6–8).…”
Section: Methodsmentioning
confidence: 99%
“…One such example in the enterobacteriaceae is the four-helix Hha-family of proteins that regulates the availability of the transcription factor H-NS 1115. Mutational studies16,17 and spectroscopic experiments provide strong evidence that Cnu (YdgT), a member of the Hha-family, exhibits graded structural polymorphism with temperature18 that could be critical for the expression of virulence genes in enterobacteriaceae by modulating the binding affinity with H-NS 19…”
Section: Introductionmentioning
confidence: 99%
“…The crude product was purified by column chromatography on silica gel (n-hexane/ethyl acetate = 85:15) and by HPLC (n-hexane/ethyl acetate = 95:5) to give 34 mg of 1b(O) in 24% yield as a pale yellow crystal. 1…”
Section: Methodsmentioning
confidence: 99%
“…11 Global spectroscopic, site-specific NMR experiments, hydrodynamic measurements, theoretical modeling, and simulations indicate that the Cnu native ensemble is best described by an array of conformational states that are in dynamic equilibrium with one another in a single broad native well. If this is indeed the case, then solvent modulations with chemical denaturants together with thermal perturbations should result in nontrivial effects on the folding landscape.…”
mentioning
confidence: 99%
“…In this regard, it was recently identified that the four-helix bundle protein Cnu ( Figure 1 a), a single gene product, displays thermosensor-like properties that are critical for efficient pathogenic response in enterobacteriaceae that commonly infect human gastrointestinal tracts. 11 Global spectroscopic, site-specific NMR experiments, hydrodynamic measurements, theoretical modeling, and simulations indicate that the Cnu native ensemble is best described by an array of conformational states that are in dynamic equilibrium with one another in a single broad native well. If this is indeed the case, then solvent modulations with chemical denaturants together with thermal perturbations should result in nontrivial effects on the folding landscape.…”
mentioning
confidence: 99%